Study of two large‐dimension Murillo's paintings by means of macro X‐ray fluorescence imaging, point X‐ray fluorescence analysis, and stratigraphic studies. (10th December 2018) - Križnar, Anabelle; Ager, Francisco J.; Caliri, Claudia; Romano, Francesco Paolo; Respaldiza, Miguel Ángel; Gómez‐Morón, María Auxiliadora; Núñez, Lourdes; Magdaleno, Rocío
Abstract : During the recent restoration of two large‐dimension paintings by Murillo, entitled "Miracle of the loaves and fishes" and "Moses and the water from the rock of Horeb, " several studies about the materials employed for their execution were carried out. Macro X‐ray fluorescence scanning technique was performed on both works complemented by point X‐ray fluorescence and stratigraphic analyses, in order to characterize the different components of the paintings (i.e., ground layer, pigments, and binders). The results allowed us to better elucidate Murillo painting technique and his creative process. Ground layer was prepared in the usual fashion of the artist, using earths, calcium carbonate, iron oxide pigments, and white lead. The polichromy is composed of lead white mixed with various pigments, depending on the colour tone to be obtained in the pictorial composition: Red and yellow ochres, vermilion, azurite, smalt, and lead‐tin yellow were the main pigments identified during our study. Finally, the presence of previous conservation treatments was evidenced by detecting pigments (zinc white, Prussian blue, etc.) not coeval with the artist palette.